DEVELOPMENT AND ANTIMICROBIAL ASSESSMENT OF NOVEL IMINE-BASED -PYRAZOLYL-1)-4,5-DIHYDROTHIAZOLYL-2)THIAZOLIDIN-4-ONE AND-PYRAZOLYL-1)-6H-1,3,4-THIADIAZINYL-2)-2-PHENYLTHIAZOLIDIN-4-ONE COMPOUNDS - Tripathi, Ajay Kumar; Singh, Saumya; Sharma, Bandana; Verma, Manoj K; Singh, Brajesh; B. K. Rathod; Srivastava, Krishna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An efficient and convenient synthesis of thiazolidinone derivatives have a pyrazolyl, dihydrothiazolyl and thiazol ring was achieved, initially prepared by chalcone (Acetophenone and o-nitro benzaldehyde) on reaction with hydrazine hydrate give cyclized product which on further reaction with thiourea and thiosemicarbazide forms II, cyclized derivatives having Schiff’s base, the thioglycolic acid and ZnCl2 in trace convert Schiff’s base into final products. The chemical structure of the synthesized derivatives has been established by elemental analysis, FT-IR, 1H NMR, and Mass spectral studies. In vitro antibacterial testing against both gram-positive and gram-negative bacteria has also been conducted on the newly synthesized TZ-4-one and PTZ-4-one derivatives using the serial tube dilution method. The newly prepared derivatives demonstrated noticeable antimicrobial properties.